Examination of criminal responsibility in children aged 12-15 - Bork, Turgay; Türkoglu, Abdurrahım; Göçük, Vahap; Tokgözlü, Ömer (My University, 2022)
This study aimed to review the sociodemographic characteristics and assess the examination results of juveniles pushed to crime (JPC) who were aged 12-15 years for whom the judicial authorities requested an opinion on criminal liability. The reports and interview forms of 100 patients. The parents were separated in 24 JPC, and 65 had four or more siblings. The average family income level was minimum wage or below in 81 cases. A review of the types of charges indicated that 56 cases were referred for theft, 47 had previous criminal records, and 17 had individuals with a history of imprisonment in their close circle. Sixteen had a history of substance abuse. Ten of 46 JPC had borderline intellectual functioning based on intelligence quotient assessment. Fifty JPC presented more than 6 months after the date of the crime. As a result of the examinations, the number of children with and without the power of discernment was 44 and 44, respectively. No decision could be made on 12 JPC because of late referral and insufficient paperwork. The minimum income level should be increased to reduce the number of JPCs. In particular, children with individuals in their close circle with a history of imprisonment should be closely monitored and necessary measures should be taken against substance abuse. Given the rapid cognitive development of children in this age group, it is difficult to make decisions when the children are referred long after the actual event.
Keywords: Kriminoloji ve Ceza Bilimi; Psikoloji; Aile Çalışmaları